Ursula Burghardt - Transgression des Alltäglichen - Rath, Jennifer (Munchen Metzel, 2022)
The sculptural work of Ursula Burghardt (1928-2008) is characterised by an ongoing exploration of the ordinary. Using a wide variety of materials and techniques, she shaped, modified and transformed everyday objects into surprising works that undermine visual habits. In this way, Burghardt created a total of 140 sculptures between 1965 and 1970, which form the core of her sculptural oeuvre and are the focus of this study. Together with her husband Mauricio Kagel, one of the most important composers of New Music, she enlivened the vibrant Rhineland cultural scene of the 1960s, exhibited with Fluxus greats such as Wolf Vostell and Nam June Paik and collaborated with Joseph Beuys, Dieter Roth and Stefan Wewerka. The dissertation analyses Burghardt's works in the light of the object-oriented art scenes of Pop Art, Nouveau Réalisme and Fluxus and shows the extent to which this sculptor succeeded in developing a formal language that was as independent as it was diverse in different groups of works. At the same time, her work extends beyond the pure objectivity. Intermedial projects, such as the film "Ludwig van" or the actionist alliance "Labor zur Erforschung akustischer und visueller Ereignisse e.V.", which she helped to create, were also intended to help bring art into society.Burghardt's work oscillates between cheerful and enigmatic, playful and critical of the times. As a sculptor, she operated in a male-dominated art world, so that socio-political and consumer-critical aspects are interwoven in her oeuvre just as much as art-inherent questions are linked with gender-specific ones. In this respect, it is surprising that her work did not receive greater attention during her lifetime. Only recently have her works found their way into important museums of contemporary art such as the Hamburger Bahnhof in Berlin and the Museum Ludwig in Cologne.This dissertation is the first comprehensive systematic classification of Ursula Burghardt's sculptural works. In addition to the art-scientific analysis, all sculptures have been made accessible for future research in a valid oeuvre catalogue. Likewise, the illustration of her contribution to the development of Mauricio Kagel's instrumental theatre holds new insights for musicology. The new perspectives opened up here not only exemplify the work of an artist in a culturally highly dynamic environment. In the sense of her own claim to "grasp the given actuality", the works fed by her direct observation and experience show in an impressive way how the personal can become the political.Translated with www.DeepL.com/Translator
Keywords: Esthetics; Fine art; Artistic research; Catalog